Supplementation of Nellore young bulls on Marandu grass pastures in the dry period of the year - Roth, Marcella de Toledo Piza [UNESP]; Resende, Flávio Dutra de [UNESP]; Siqueira, Gustavo Rezende [UNESP]; Fernandes, Rodolfo Maciel; Custódio, Letícia; Roth, Anna Paula de Toledo Piza [UNESP]; Moretti, Matheus Henrique [UNESP]; Campos, Wellington da Costa de (Sociedade Brasileira de Zootecnia, 2013)
The objective of this study was to evaluate performance and daytime ingestive behavior of 84 Nellore young bulls in the post-weaning phase kept on Brachiaria brizantha cv. Marandu pastures during the dry season. Treatments were protein mineral supplementation (1 g/kg body weight) and protein+energy mineral supplementation (3 g/kg body weight). The experimental area comprised 12 paddocks in a total area of 27.36 ha, divided in two blocks of six paddocks each, having three replications per treatment in each block, with 42 animals/treatment. The data were subjected to variance analysis with repeated measures over time via procedure PROCMIXED of SAS (Statistical Analysis System, version 9.0) and means were compared by the Tukey test at 5% probability. The initial average weight of animals was 204.8 kg; final weights were 260.9 and 276.9 kg for animals that received protein and protein+energy supplement, respectively. The forage availability, sward height and stocking rate values did not differ with supplementation, but they showed difference between the experimental periods. The average time spent grazing during daylight of animals fed protein+energy supplement was shorter as compared with those which consumed protein supplement. Animals kept under the same pasture conditions during the dry season show better performance when they receive protein+energy supplement than protein supplement.
Keywords: animal performance; Brachiaria brizantha; post-weaning phase